2011
DOI: 10.1016/j.jpsychires.2011.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Medial temporal structures and memory functions in adolescents with heavy cannabis use

Abstract: Converging lines of evidence suggest an adverse effect of heavy cannabis use on adolescent brain development, particularly on the hippocampus. In this preliminary study, we compared hippocampal morphology in 14 "treatment-seeking" adolescents (aged 18-20) with a history of prior heavy-cannabis use (5.8 joints/day) after an average of 6.7 months of drug abstinence, and 14 demographically matched normal controls. Participants underwent a high-resolution 3D MRI as well as cognitive testing including the Californi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
200
9
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 216 publications
(221 citation statements)
references
References 124 publications
(120 reference statements)
9
200
9
3
Order By: Relevance
“…There is growing evidence that long-term or heavy cannabis use impacts upon brain structure and function, particularly in regions known to be affected in schizophrenia, such as the hippocampus (Ashtari et al, 2011;Lorenzetti et al, 2010;Solowij and Michie, 2007;Solowij et al, 2012). We have previously reported doserelated reductions in hippocampal volume in otherwise healthy chronic cannabis users that were associated with subclinical positive psychotic symptoms (YĂŒcel et al, 2008), and were of a magnitude similar to that observed in schizophrenia (e.g.…”
Section: Introductionmentioning
confidence: 85%
“…There is growing evidence that long-term or heavy cannabis use impacts upon brain structure and function, particularly in regions known to be affected in schizophrenia, such as the hippocampus (Ashtari et al, 2011;Lorenzetti et al, 2010;Solowij and Michie, 2007;Solowij et al, 2012). We have previously reported doserelated reductions in hippocampal volume in otherwise healthy chronic cannabis users that were associated with subclinical positive psychotic symptoms (YĂŒcel et al, 2008), and were of a magnitude similar to that observed in schizophrenia (e.g.…”
Section: Introductionmentioning
confidence: 85%
“…Of the seven studies comparing global brain volume measures between chronic cannabis users and healthy controls, there was only one study reporting significant differences [143], namely reduced ventricular cerebral spinal fluid (CSF) in cannabis users. Another study [145] reported total brain volume difference between groups which was no longer significant when the authors covaried for confounding factors such as premorbid intelligence.…”
Section: Structural Neuroimaging Studies In Adult Chronic Cannabis Usersmentioning
confidence: 97%
“…Structural differences were obtained in seven of them in terms of global brain measures [143] or gray/white matter changes [144][145][146][147][148][149]. Four studies did not find any significant structural alterations when comparing chronic cannabis users with healthy controls [150][151][152][153].…”
Section: Structural Neuroimaging Studies In Adult Chronic Cannabis Usersmentioning
confidence: 99%
See 2 more Smart Citations